Evaluating the effects of a standardized polyphenol mixture extracted from poplar-type propolis on healthy and diseased human gut microbiota. - Garzarella, Emanuele Ugo; Navajas Porras, Beatriz; Pérez-Burillo, Sergio; Ullah, Hammad; Esposito, Cristina; Santarcangelo, Cristina; Hinojosa Nogueira, Daniel; Pastoriza, Silvia; Zaccaria, Vincenzo; Xiao, Jianbo; Rufián-Henares, José Ángel; Daglia, Maria (Elsevier, 2022)
Introduction: A large body of evidence suggests that propolis exerts antioxidant, anti-inflammatory, and antimicrobial activities, mostly ascribed to its polyphenol content. Growing evidence suggests that propolis could modulate gut microbiota exerting a positive impact on several pathological conditions. The aim of this study was to determine the in vitro impact of a poplar-type propolis extract with a standardized polyphenol content, on the composition and functionality of gut microbiota obtained from fecal material of five different donors (healthy adults, and healthy, obese, celiac, and food allergic children). Methods: The standardized polyphenol mixture was submitted to a simulated in vitro digestion-fermentation process, designed to mimic natural digestion in the human oral, gastric, and intestinal chambers. The antioxidant profile of propolis before and after the digestion-fermentation process was determined. 16 S rRNA amplicon next-generation sequencing (NGS) was used to test the effects on the gut microbiota of propolis extract. The profile of the short-chain fatty acids (SCFA) produced by the microbiota was also investigated through a chromatographic method coupled with UV detection. Results: In vitro digestion and fermentation induced a decrease in the antioxidant profile of propolis (i.e., decrease of total polyphenol content, antiradical and reducing activities). Propolis fermentation exhibited a modulatory effect on gut microbiota composition and functionality of healthy and diseased subjects increasing the concentration of SCFA. Conclusions: Overall, these data suggest that propolis might contribute to gut health and could be a candidate for further studies in view of its use as a prebiotic ingredient.
Keywords: Acidos grasos; Digestión; Antioxidantes; Flora intestinal; Propóleos; Poplar-type propolis; Multi dynamic extraction; In vitro digestion; In vitro fermentation; Antioxidant capacity; Gut microbiota; Short-chain fatty acids